Features of pancreatic lesions on the background gastroduodenal pathology associated with H.pylori-infection - T.V. Sorokman; O.-M.V. Popelyuk; O.V. Makarova; N.Ya. Vaskul (Zaslavsky O.Yu., 2017)
Background. There are recent publications about the possible impact of Helicobacter pylori (H.pylori) on the mucous membrane of the stomach or duodenum, as well as the pancreas. This relation is theoretically possible considering the close connection of stomach, duodenum and pancreas. The purpose of the study was the determination of the incidence and characteristics of combined lesions of the pancreas and the upper gastrointestinal tract associated with H.pylori infection in children. Material and methods. A retrospective analysis of medical records of 684 children, who were hospitalized in the gastroenterology department of the Chernivtsi regional children's hospital during the period from 2010 to 2016. A comprehensive examination included ultrasound diagnostics of the abdomen, esophagogastroduodenoscopy, determination of the activity of serum α-amylase, urine diastase, coprogram assessment. A test system HELIC-test "AMA" (Russia, St. Petersburg) and histological methods (bioptates were taken from the fundal and antral gastric mucosa, after Giemsa stain of histological sections, the visualization of H.pylori was performed by means of light microscopy) were used for the H.pylori diagnosis. The descriptive statistics methods with parametric distribution estimating the mean and standard deviation (M ± SD) were applied. Statistical significance of differences was assessed by Student's t-test for independent samples. Results. Of the 684 children, who completed a survey, 310 were boys (45.3 %) and 374 - girls (54.7 %) aged 6 to 18 years. The diagnosis of chronic gastroduodenitis was the most frequently registered among examined children (420 out of 684 patients examined, 61.4 %). A rather high number of children had erosive and ulcerative lesions of the stomach and duodenum (157 of 684 patients, 22.9 %). H.pylori infection in a group of the children surveyed was detected in 64.5 % cases. The highest incidence of H.pylori was in children with ulcerative-erosive lesions of the upper gastrointestinal tract - 121 of 157 analyzed, 77.1 %. In more than half of patients (352 of 684 patients, 51.5 %) with gastroduodenal pathology, the pancreas was also involved in the pathological process. In 56.8 % of those with combined lesions, a test for H.pylori was positive. H.pylori was most frequently detected in patients with erosive and ulcerative lesions of the upper gastrointestinal tract and lesions of the pancreas (92 of 119 examined patients, 77.9 %). Patients with H.pylori positive test had 5.1 ± 1.2 points of pain syndrome intensity, whereas those with H.pylori negative test - 2.8 ± 1.0 points (p < 0.05). The manifestations of the neurasthenic syndrome (dizziness, fatigue, drowsiness, sleep disturbances, reduced work capacity and weakness) prevailed in children with H.pylori positive test. Increasing of the pancreatic size was seen in one-third of patients, altered echogenicity - in 28.8 % of cases, blurred contours of gland - in 23.6 %. Increased activity of serum α-amylase was found in 44.8 %. Changed levels of urine diastase were observed in 90 (45.4 %) infected patients and in 36 (23.3 %) - uninfected (p < 0.01) with H.pylori. Changes in the coprological test were seen in 130 of 352 children (36.9 %), namely, steatorrhea was observed in 27.4 % of cases, creatorrhea - in 22.6 %, starch in large quantities - in 12.9 %, mucus - in 9.6 %, iodophilic and fungal flora were found in 16.1 and 18.5 % of children, respectively. Conclusion. More than a half of children with gastroduodenal pathology, according to the data of retrospective analysis, have impaired exocrine pancreatic function, which is diagnosed by means of generally accepted clinical laboratory and instrumental methods. Such violations are more often recorded in H.pylori-associated pathologies of the upper digestive tract, the pain and cerebro-asthenic syndromes prevailed in clinical picture, especially in case of erosive and ulcerative lesions of the mucous membrane of the gastroduodenal region. This necessitates an in-depth study of pancreatic function in children with H.pylori-associated gastroduodenal pathology.